Faith's mountain home - Beller, Misty M. (Beller, Misty M. Hearts of Montana, 2021)
"In 1867, Nate Long has always watched over his twin, even if it's led him to be an outlaw. When his brother is wounded in a shootout, it's their former prisoner, Laura, who ends up nursing his wounds at Settler's Fort. She knows Nate wants a fresh start, but struggles with how his devotion blinds him. Do the futures they seek include love, or is too much in the way?"--